Design, Synthesis, and Cytotoxicity Evaluation of 3‐(5‐(3‐(aryl)‐1‐phenyl‐1H‐pyrazol‐4‐yl)‐1‐phenyl‐4, 5‐dihydro‐1H‐pyrazol‐3‐yl)pyridine and 5‐(3‐(aryl)‐1‐phenyl‐1H‐pyrazol‐4‐yl)‐3‐(pyridin‐3‐yl)‐4, 5‐dihydropyrazole‐1‐carbaldehyde Derivatives as Potential Anticancer Agents. (16th September 2016) - Alam, Raquib; Alam, Md. Aftab; Panda, Amulya K.; Rahisuddin,
Abstract : In an attempt to find bio‐active small molecules, a series of novel 3‐(5‐(3‐(aryl)‐1‐phenyl‐1H‐pyrazol‐4‐yl)‐1‐phenyl‐4, 5‐dihydro‐1H‐pyrazol‐3‐yl)pyridine5a–i and 5‐(3‐(aryl)‐1‐phenyl‐1H‐pyrazol‐4‐yl)‐3‐(pyridin‐3‐yl)‐4, 5‐dihydropyrazole‐1‐carbaldehyde6a–i were designed, synthesized, and evaluated for their in vitro cytotoxic activity against a panel of human cancer cell lines namely; HeLa (human cervix), NCI‐H460 (human lung), PC‐3 (human prostate), and NIH‐3T3 (mouse embryo fibroblasts) normal cell line. Most of these compounds exhibited moderate to good cytotoxic activity against the tested cancer cell lines and weak toxicity against normal cell line. Analogues5b, 5f, 5g, 6b, and6g showed significant cytotoxicity as compared to standard drug etoposide. Among all the synthesized compounds, compound6g displayed superior cytotoxicity with an IC50 value of 7.98 ± 1.08 μM for Hela cancer cell line. Abstract :